Organ donation as an outcome of traumatic cardiopulmonary arrest: A cost evaluation. Issue 5 (May 2016) - Love, Katie M.; Brown, Joshua B.; Harbrecht, Brian G.; Muldoon, Susan B.; Miller, Keith R.; Benns, Matthew V.; Smith, Jason W.; Baker, Christopher E.; Franklin, Glen A.
Abstract : BACKGROUND: Survival after traumatic cardiopulmonary arrest (TCPA) is rare and requires significant resource expenditure. Organ donation as an outcome of TCPA resuscitation has not yet been included in a cost analysis. The aims of this study were to identify variables associated with survival and organ donation after TCPA, and to estimate the cost of achieving these outcomes. We hypothesized that the inclusion of organ donation as a potential outcome would make TCPA resuscitation more cost-effective. METHODS: Adult patients who required resuscitation for TCPA at a level I trauma center were retrospectively reviewed over 36 months. Data were obtained from medical records, hospital accounting records, and the local organ procurement agency. Outcomes included survival to discharge, neurologic function, and organ donor eligibility. An individual-level state-transition cost-effectiveness model was used to evaluate the cost of TCPA resuscitation with and without organ donation included as an outcome. Incremental cost-effectiveness ratio was calculated to determine additional cost per life saved when organ donation is included. RESULTS: Over the study period, 8, 932 subjects were evaluated. Traumatic cardiopulmonary arrest occurred in 237 patients (3%). The mortality rate was 97%. Variables associated with survival included emergency department disposition to the operating room ( p < 0.01) and reactive pupils ( p < 0.001). Of seven survivors, four were discharged neurologically intact. Of the patients with TCPA, 5% were eligible for organ donation with a procurement rate of 2%. Organ donor eligibility was associated with arrest after arrival to the emergency department ( p < 0.01) and transfusion of fresh frozen plasma ( p = 0.01). The cost of TCPA resuscitation per survivor was $1.8 million; cost per survivor or life saved by donation was $538, 000. The incremental cost-effectiveness ratio was $76, 816 per additional life saved including donation as an outcome. CONCLUSION: The decision to pursue resuscitation should continue to be based on the presence of signs of life, especially pupil reactivity and duration of arrest. If the primary objective is survival, organ procurement will be maximized without conflict of interest. Early fresh frozen plasma transfusion may increase successful organ donation. The financial burden of TCPA resuscitation can be mitigated by expanding end points to include organ donation. LEVEL OF EVIDENCE: Prognostic and epidemiologic study, level III; cost analysis, level V.